O garimpo virtual e a extração de raridades para a continuidade da cultura do antigomobilismo: fatores que levam os colecionadores de veículos antigos a comprarem peças de reposição pela internet - Weiler Neto, Roberto (2022)
This research enhances the existing literature about trust, risk and word-of-mouth (WoM) on online market, integrating these factors with the technology adoption model and its connections to ease of use and perceived usefulness. With this, it is argued that the purchasing intention in the context of e-commerce for collectors of antiques, consumer focus of this study, can be better understood by evaluating such motivating and inhibiting factors to the online purchase of spare parts. It is also part of this research, understand how the generation of emotional and positive nostalgic feelings are connected in this purchasing process. The study proposes qualitative research with collectors of antique vehicles through sixteen in-depth interviews limited by the saturation criteria, in order to understand the behavior of these consumers in their purchasing journey. Data were collected, stored, and analyzed using Atlas TI software and compared with the theory previously raised. The results show that the main motivating and inhibiting factors for buying auto parts over the internet in order of significance are trust, ease of use, perceived risk, positive word-of-mouth, perceived usefulness and negative word-of-mouth. It is also suggested that online shopping has a relevant role in the process of mining auto parts and the unavailability of parts for collection vehicles, makes the internet considered as fundamental tool for the continuity of the antique vehicle culture. Although, trust is a highly relevant component to influence purchasing intention, there are interrelationships between these factors. Ease of use influences perceived usefulness, both influence trust. Ease of use influences word-of-mouth, which when positive influences trust and when negative influences perceived risk. Finally, risk negatively influences trust and this, in turn, positively influences risk. There are important influencing components that support the main motivators and inhibitors in determining online purchasing intention, which were also explored and part of this study. Finally, the results also showed that the generation of emotions emerged before and after online purchasing. The generation of emotions resulting from finding and/or purchase a product online, represents to the collector an intense interest and the guarantee to keep the collection working, consequently promoting a load of positive nostalgic experiences that refers to the collector´s past feelings of good memories.